Giant cystic leiomyoma with uterine location: A case report (Annals of Medical Research, 2021)
The uterine leiomyomas frequently encountered in gynecological practice originate from myometrial smooth muscle cells and can range in size from microscopic to huge. Giant leiomyomas are extremely rare and can be confused with ovarian or localized retroperitoneal neoplasias due to their nonspecific clinical presentation and degeneration. Herein, we report a 41-year-old patient who presented with irregular menstruation and abdominal pain. Ultrasonography revealed a solid mass located between the uterus and the bladder with cystic areas measuring 21×18 cm. Total abdominal hysterectomy and left salpingo-oophorectomy were performed. In the macroscopic examination, a 1300 g, 21×18×6-cm cystic structure with a multiloculated appearance and solid areas was observed. On histopathological examination, the patient was diagnosed with a leiomyoma with cystic degeneration. She was discharged on the second postoperative day without complications.